Teacher Education Freshmen Applicants’ Current State in the New Normal’s Learning Delivery Platforms - Mark Angelo C. Reotutar (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2020)
The online learning platform (OLS) is currently the new normal learning setting amidst the Covid-19 pandemic. Teachers need to look on the other side of the traditional classroom-based learning mode to make teaching and learning in the new normal possible. It aimed to analyze the current state of the teacher education freshmen applicants concerning the new normal learning platforms. This study employed a descriptive method of research and considered a sample of 85 freshmen applicants in the College of Teacher Education in the academic year 2020-2021. The frequencies and percent value was used to analyze the data gathered. The following are the verdicts of the study, the bulk of the respondents belong to low-income families with farming as their family source of income. Most of the respondents have their mobile phones while the great majorities are using mobile data only. All of the respondents do not have any idea about the different platforms in online learning. Based on the findings, the researcher concluded that the freshmen applicants in the College of Teacher Education cannot totally survive and are not yet ready to embrace the new normal learning platforms due to poverty and lack of resources. It is therefore recommended that the University administration needs to open other sources of learning platforms such as the use of printed learning materials of which will be delivered door-to-door to the students. Besides, the College of Teacher Education should plan and initiate on how to make learning flexible and more engaging.